The importance of nutritional support.: Nuestra experiencia - Cúneo, Roberto (Cirugía del Uruguay, 1988)
Authors present local experience in the use of artificial nutritlon techniques in 35 patients suffering from serious illness, most of them in situations of hyperca• taboiism. They make a revision of natlonal and international schools' concepts on the importance of nutri• tlonai support and polnt out the need to use an adequate prospectiva protocol according to the different environments in order to rationalize lndications and make patients' cllnical, antrometrical and biological follow up better.